ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENDATAAN KELUARGA PENERIMA MANFAAT (KPM) BANTUAN PANGAN NON TUNAI (BPNT) PADA DINAS SOSIAL KOTA JAMBI - Rahmadani, M. Irsyad; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2019)
The Social Service Office of Jambi City faces difficulties in registering the people who receiving non-cash food assistance. Data collection is still done conventionally so that it allows errors in the process of data input, multiple identities, files build up, sometimes files are easily lost and difficult to find. This problem causes the author to provide a solution in the form of a website-based KPM BPNT Data Information System using Use Case Diagrams, Activity Diagrams and Class Diagrams as a system design model. The design of the system is only limited to a prototype. The results obtained in the form of a Draft Information System for KPM BPNT Information for Jambi City Social Service Office which can be implemented further so as to produce a data information system that supports the data collection activities of the Jambi City Social Service Ofice